Aspectos da biologia de Zygocotyle lunata (Trematoda: Zygocotylidae) isolado de Biomphalaria straminea (Mollusca: Planorbidae) oriundas de iguatama, Minas Gerais, Brasil - Fernando Sergio Barbosa (2011)
Malacological collections were carried out in lakes near the São Francisco River or its tributaries in Iguatama (Minas Gerais), in the last trimester of 2009, and second and third trimester of 2010. From 4993 mollusks samples collected, 4307 were alive and forwarded to analysis. From the alive ones, 71 samples (1.65%) were infected by trematodes larvae that, after preliminary morphological characterization, were used for experimental biological studies. Life stages (cercariae, metacercariae, adult parasites, eggs and miracidia) were studied before and afterundergoing the process of fixation, staining and mounting on permanent slides, followed by morphological and morphometric analysis with light microscopy. Anfistoma-like cercariae were found in 14 specimens (0,33%) of Biomphalaria straminea which, after turning into metacercariaon solid substrate, were used to check viability in performing experimental infections in AKR/J mice, Gallus gallus domesticus and Meriones unguiculatus. Viability of metacercaria that encisted in 1, 30 and 120 days was checked; however, those of 150 days could not infect. Animals experimentally infected presented parasite eggs in stools from 30 days post-infection that were used to obtain miracidia for infections of mollusks. The hatching of miracidia happened 21 days after infection. Adult parasites retrieved from the cecum region of experimentally infected animals were analyzed, measured and identified as Zygocotyle lunata(Diesing, 1836). Effects of dexamethasone treatment during the course of experimental infection of Mus musculus were also evaluated. It was verified in animals treated with dexamethasone a reduction of the prepatent period and a higher number of parasites, although with smaller size. Descendants of mollusks collected in Iguatama (B. straminea, Physa marmorata, Pomacea caniculata, Drepanotrema anatinum), Belo Horizonte, MG (B. glabrata), Felixlândia, MG and Recife, PE (B. straminea) were exposed to massive and individual infection with miracidia of Z.lunata, and success was obtained only in B. straminea. This is the first record of B. straminea naturally infected by Z. lunata in Brazil.